A framework for secure online exam using biometric fingerprint and steganography technique in National Open University, Nigeria - Ahmed Isah Baba
Online exam user authentication is a critical security issue. The traditional techniques of authentication that usually rely on object-based methods (such as token, smart card, ATM card) and knowledge-based methods (such as secret password, challenge questions) suffered a lot of drawbacks such as' stealing, forgetting, forgery, and impersonation. These drawbacks pose a lot of problems to the online exams, which leads to the use of biometrics, steganography and cryptography techniques. This thesis adopt the three techniques named multi-layer approach to the security framework for online exam authentication in National Open University of Nigeria using a combination of Discrete Wavelet Transform and Least Significant Bit. The DWT was applied for all colors layers (Red, Green, and Blue) separately for both cover and secret image with different levels; 1 - level for the secret im age and 3 - level for cover image where encrypted coefficients of sub bands of the secret image are embedded in the corresponding subbands of the Cover linage. The least Significant is applied in two stages. The first stage is to choose the best cover image that will be used to conceal the secret image, while the second stage is to choose the best embedding threshold that will be used to determine the embedding locations in both embedding and extraction phases. The whole examination process can be divided into two phases namely student registration and student login. During registration, the student will be asked for name, fingerprint image, and email address. In return, the student will be given an exam TD, Personal Authentication Number (PAN), a secret key and his fingerprint image. The server makes use of Least Significant Bit (LSB) technique to form a signature (Stego-image) for each student by embedding the PAN (secret message) into the fingerprint linage (cover-image) and have it stored into the database. On the examination day, the examinee sits in front of an internet-enabled computer, enters the exam ID into the university site followed by request for his fingerprint image which was exchanged during the registration and saved into the USB device, the secret key and the PAN via a series of request and response messages. These three items will be compared to that stored in the database. Respectively, if they are identical, the examinee is authenticated and allowed to proceed to the examination. The results obtained from the experimentation shows that a Peak Signal to Noise Ratio (PSNR) ranges from 66.21dB - 68.10dB, Mean Square Error (MSE) of 0.60023 - 0.70147 and Normalized Cross - Correlation (NCC) of 0.9752 - 0.9935 for the Improved Least Significant Bit. These values give a good quality of the Stego-image, and hence the embedded secret message is difficult to be detected by attackers. Moreover, the multi-layer nature of the framework's security which combined the secret key, PAN and fingerprint image make the system secure and difficult to be tempered by any intruders. Hence, the proposed method guarantees the security of online examination procedures against a variety of fraudulent conducts.